A STUDY OF REQUESTS AND RESPONSES IN ENGLISH PERFORMED BY AMERICAN AND VIETNAMESE HOTEL RECEPTIONISTS - Ph. D. Tran Quang Hai (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
This study identifies and discusses similarities and differences in request and response expressions, request and response strategy use and the effect of interlocutor status on request and response strategy used by American and Vietnamese hotel receptionists. It also points out and discusses the relationship of politeness strategy use. Some teaching activities were designed as samples for effective communications in hotels.